PENGARUH PRAKTIK PERTANIAN ORGANIK DAN SEMI ORGANIK TERHADAP BEBERAPA SIFAT TANAH DI LERENG SELATAN GUNUNG MERAPI - Amsyah Pratama; Miseri Roeslan Afany; Muhamad Kundarto (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
Volcanic activity provides fertility for the land on the slopes of Merapi. The material from the eruption of Merapi contains many nutrients. The fertility of the Merapi area is used by the people on the slopes of Merapi to grow vegetable and fruit crops. This study aimed to determine the influence of organic and semi-organic farming practices on several soil properties on the southern slopes of Mount Merapi. This research used a survey method. Research locations on organic farming practices in Tani Organik Merapi (TOM), semi-organic farming practices 1 in Indmira and semi-organic farming practices 2 at UPTD BP3MBTP Ngipiksari. Determination of sample points was carried out purposively based on their agricultural practices. Sample points in organic farming practices, semi-organic 1 and 2 as many as 9 sampling points. After that, the physical, chemical, and biological properties of the soils were analyzed ina laboratory. The results of this study showed that organic farming practices could increase soil pH, caciton exchange capacity (CEC) and the number of bacteria.